1968 Enrico Fermi Award Presentation - Lawrence Berkeley National Laboratory. Technical and Electronic Information Department (1968)
Black and white photograph depicting Glenn Seaborg (1912-1999) and President Lyndon B. Johnson (1908-1973) presenting the Fermi Award to Dr. John Wheeler (1911-2008) at the White House. Wheeler was an American theoretical physicist who is known for his work in general relativity, the development of the Breit-Wheeler process, and for coining the term "black hole." The Enrico Fermi Presidential Award is one of the oldest and most prestigious science and technology honors bestowed by the U.S. Government. The Fermi Award is annually conferred by the President of the United States to honor scientists, engineers, or science policymakers who have achieved excellence in research in energy science and technology benefiting mankind.
Keywords: Seaborg, Glenn T. (Glenn Theodore), 1912-1999; Wheeler, John Archibald, 1911-2008; Johnson, Lyndon B. (Lyndon Baines), 1908-1973; Nobel Prize winners; Science--Awards